Beyond the Nation State: The Transnational Turn in Holocaust Studies (KULT_online, 2018)
The extensive volume Entangled Memories. Remembering the Holocaust in a Global Age integrates manifold disciplinary backgrounds – from architecture, literary and film studies to ‘Holocaust Education’ and its musealization. The volume positions itself between the tension of an increasing transnationalism in the field of memory studies and the persistence of the nation state to define commemorative practices in opposition to a globalized Holocaust memory. The edited volume thus aims at depicting different national remembrance cultures in their relation to supra- and subnational perspectives. While the volume successfully displays the multitude of literary, architectural, visual and theatre representations of the Holocaust, the meaning of “entanglement” could have been followed more profoundly to bind the different articles together theoretically.